Progress in the Production of Phenyltrichlorosilane via Gas Phase Condensation Method - Le, Huang; Zhihui, Jin; Gengxin, Xu; Yingxin, Liu; Zuojun, Wei (Current Organic Chemistry, 2026)
Phenyltrichlorosilane is an important organosilicon compound, and its synthesis technology is a key research focus in the field of organosilicon chemistry. This article introduces the three main techniques for synthesizing phenyltrichlorosilane: the Grignard reagent method, the direct method, and the vapor phase condensation method, along with their respective advantages and disadvantages. It demonstrates that the vapor phase condensation method has become the dominant process due to its simple reaction apparatus and the feasibility of achieving continuous production. However, this method faces significant challenges, including low yield and the formation of carbon deposits within production pipelines. The process conditions of the vapor phase condensation method are summarized, including the reaction conditions of chlorobenzene and trichlorosilane at 540-680°C, which achieves a product yield of up to 65%. This study provides an in-depth analysis of the decomposition mechanism of trichlorosilane and chlorobenzene under high-temperature vapor-phase conditions, emphasizing the synthesis mechanism of phenyltrichlorosilane and analyzing the role of free radical initiators and their impact on enhancing the yield of phenyltrichlorosilane. Future research should focus on the development of new catalysts and initiators, process optimization, and the expansion of phenyltrichlorosilane's application fields.
Keywords: trichlorosilane